(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Business intelligence (BI) is basically a collection of programs, utilities and apps that allows you to analyze large quantities of data (Big Data). Every year, educational institutions deal with enormous amounts of Big Data. The use of business intelligence (BI) in these organizations is critical for improving processes and supporting decision-making. A Datawarehouse is the foundation of every BI project (DW). The scheme deliberations for implementing DW in any of the institutional setting are described in this article. Using educational data mining (EDM) methods, the DW shall be utilized in an information unearthing procedure to manage the statistics and facts for the study of vital accomplishment metrics. A knowledge management framework’s main technical assets are a data warehouse (DW) and an enterprise architecture (EA) repository (KMF). The agenda further was created to provide order to the processes of knowledge generation, capture, transfer, and digitization. This handbook and the framework are two of the results of a private university’s research effort. In addition, an illustrative example demonstrates picking of the finest technique in higher education. The stages for DW design are given in the case study. This research may help academics and practitioners who want to create a data warehouse to analyze data utilizing EDM methods.